1994
DOI: 10.1207/s15327752jpa6302_10
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Family-Environment Predictors of Self-Reported Eating Attitudes and Behaviors

Abstract: We assessed the contributions of personality and family environment to variations in self-reported eating attitudes and behaviors. Female college undergraduates (N = 137) completed the NEO Personality Inventory (NEO-PI; Costa & McCrae, 1985), Family Environment Scale (Moos & Moos, 1986), Eating Disorder Inventory (EDI; Garner & Olmsted, 1984), and revised Eating Attitudes Test (EAT-26; Garner, Olmsted, Bohr, & Garfinkel, 1982). Correlation and multiple regression analyses showed that among the personality vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
4

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 1 publication
(1 reference statement)
7
66
4
Order By: Relevance
“…Our prevalence of high scorers (8.4%) was also lower than figures reported for female students from other university samples, ranging from 17 to 21.9% 16,17,64,67 . These results indicate that disordered eating is possibly not such a prominent concern during a student's first year.…”
contrasting
confidence: 81%
“…Our prevalence of high scorers (8.4%) was also lower than figures reported for female students from other university samples, ranging from 17 to 21.9% 16,17,64,67 . These results indicate that disordered eating is possibly not such a prominent concern during a student's first year.…”
contrasting
confidence: 81%
“…This corroborates longitudinal research which found that personality prospectively predicts the development of eating pathology. [36][37][38] Taken together, findings from all three models indicate that although personality may have direct effects on disordered eating [16][17][18][19] and may be influenced by eating pathology, 39 associations between attachment and disordered eating are mediated by personality characteristics rather than the reverse.…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that sufferers of anorexia and bulimia have, compared with normal individuals, a significantly elevated level of neuroticism. 105,106,[131][132][133] The correlation between EDI subscales and neuroticism is generally so strong that it is possible to consider eating disorder symptoms an aspect of neurotic personality dispositions. 105 In culture-level analysis, several non-Western cultures such as the Japanese, Koreans, and the Chinese score very high on the dimension related to neuroticism, while many prominent Western cultures such as Americans, the Dutch, and Swedes score low on neuroticism.…”
Section: Discussionmentioning
confidence: 99%